1975
DOI: 10.1099/0022-1317-27-3-319
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis in Sendai Virus-infected Cells

Abstract: SUMMARYThe rate of protein synthesis in chicken embryo cells infected with Sendal virus 18 to 20 h previously was about two times greater than in mock-infected controls. At this time of infection six stable virus-induced proteins, four major structural proteins (P, NH, NP and M) and two non-structural proteins (28K and 6IK), were identified by electrophoresis in SDS-polyacrylamide gel of total cell extracts. The structural glycopeptide F was not detected in the infected cell extracts. Pulse-chase experiments s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
1985
1985

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For both VSV and Sendai virus, the primacy of transcriptional regulation of polypeptide abundances need not be absolute. A superimposed "fine-tuning" level of translational control has not been disproven; in fact, close inspection of our data on the relative abundance of the putative message for polypeptide L compared with available data on the abundance of polypeptide L in infected cells (24,38) suggests that this message is inefficiently translated. A similar situation may exist for the L polypeptide of VSV (15).…”
Section: Discussionmentioning
confidence: 71%
“…For both VSV and Sendai virus, the primacy of transcriptional regulation of polypeptide abundances need not be absolute. A superimposed "fine-tuning" level of translational control has not been disproven; in fact, close inspection of our data on the relative abundance of the putative message for polypeptide L compared with available data on the abundance of polypeptide L in infected cells (24,38) suggests that this message is inefficiently translated. A similar situation may exist for the L polypeptide of VSV (15).…”
Section: Discussionmentioning
confidence: 71%
“…Perhaps only one of the forms of P is a component of the transcriptase, whereas most of P may have other roles. Recently, V. Chinchar and A. Portner (personal communication) found that Sendai nucleocapsids containing a 40-kilodalton proteolytic fragment of P retained most of their enzymatic activity, suggesting either a greater enzymatic role for the L protein (19,52) or that only part of the P molecule is required.…”
Section: T: 'mentioning
confidence: 99%
“…The heavily exposed auto radiograms ( fig. 1) reveal several minor polypeptide species, which have also been described before [13,14], One of these, designated L, has recently been identified as a nucleocapsid component [12][13][14], It has a molecular weight of about 160,000 and it is apparently specified by a large (33S) messenger RNA species [13,15]. Unfortunately, considering its probable relevance to Sendai virus nucleocapsid functions, it was present in insufficient amounts in our preparations to permit tryptic peptide analyses.…”
mentioning
confidence: 95%
“…The labeled virion and nucleocapsid polypeptides were resolved in typical fashion by discontinuous SDS-PAGE [11][12][13][14] as shown in figure 1. The major virion polypeptides, P, HN , F", NP.…”
mentioning
confidence: 99%